Analysis of Murabahah Contract Financing in the Covid-19 Pandemic Era at Koperasi Serba Usaha Bmt Al-Iqtishady Pagesangan Mataram - Ade Shofiatun Sholehah; Nur aeda; Baihaqi (International Journal of Islamic and Social Sciences (ISOS), 2021)
The purpose of this study was to determine the impact of the COVID-19 pandemic on financing in murabahah contracts and the way the Koperasi Serba Usaha Bmt Al-Iqtishady Pagesangan Mataram in overcoming these impacts, especially related to problematic financing. The type of research approach used is descriptive qualitative with data collection methods including: observation, interviews and documentation, while the data analysis methods used are data collection, data reduction and verification. The results of this study show (1) the impact of the covid-19 pandemic on murabahah financing is a change in the transaction method, a decrease in the amount of murabahah financing disbursed as a result of increasing cooperative prudence, the occurrence of problematic financing caused by the business or work of customers affected by the Covid pandemic. -19 thus affecting the ability of customers to pay their obligations. (2) the method used by the Koperasi Serba Usaha BMT Al-Iqtishady Pegesangan Mataram in overcoming the impact of the Covid-19 pandemic, namely by restructuring problematic financing, including: rescheduling, namely by rescheduling the due date by giving an extension of time, the return requirement is by rescheduling re-arrangement of the installment amount, term and schedule of payments, and the last is realignment, namely by changing the form of the murabahah financing contract into other contracts such as mudharabah or musyarakah.